Altitudinal migration in bats: evidence, patterns, and drivers - McGuire, Liam P.; Boyle, W. Alice (My University, 2014)
Altitudinal migrations are common in all major vertebrate and some invertebrate lineages. Such migrations have important implications for the basic and applied ecology of animals making these movements. The idea that bats make altitudinal migrations has been suggested for nearly a century. However, studies documenting the existence and causes of altitudinal bat migrations are scarce, and are frequently published in the ‘grey’ literature. For the first time, we comprehensively review the evidence supporting the existence of altitudinal bat migrations worldwide, describe basic patterns of migration in temperate and tropical regions, and articulate and propose tests of hypotheses potentially explaining these migrations. We compiled a list of 50 studies indicative of altitudinal bat migration in 61 species (five families) from 21 countries (four continents). The temporal and spatial patterns of these migrations grouped biogeographically. Temperate bats generally exhibit sex-biased migrations with females inhabiting lower elevations than males during reproductive periods. Although there is less information on tropical bat migration, few studies report sex-biased migration. We compiled hypotheses proposed in the bat and (more extensive) avian literature to provide a list of hypotheses potentially explaining altitudinal bat migrations. These hypotheses rely upon temporal availability of (and competition for) food resources, spatial distribution of geomorphological features suitable for hibernation, sex-related differences in the use of torpor, mating opportunities, and climatic factors that impose direct physiological challenges to survival or that restrict the ability to forage. A more thorough description of the migration patterns of most species will be required to distinguish effectively among these hypotheses. We identify research avenues that would broaden our understanding of bat migration patterns and provide critical information required for effective conservation.
Keywords: Partial migration; Differential migration; Sexual segregation; Bats; Chiroptera; Evolution of migration; Seasonal movements